Electrochemical properties of copper and silver electroexplosion powders; Fizika i Khimiya Obrabotki Materialov; № 3 - Ilyin A. P. Aleksandr Petrovich (1995, 1995)
The state of electronic subsystem of copper and silver ultra-fine powders produced by wires electric explosion in argon environment was studied. Using the method of inversion voltammetry current a peaks shift of/and additional maximums appearance was found in the negative potentials range. At least part of stored explosion energy in ultrafine powders was shown to be connected with their charge structure. Investigations were carried out on 50 copper specimens produced in different conditions.